2018
DOI: 10.1039/c8ra04254c
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated covalent triazine-based frameworks as catalysts for the hydrolysis of cellobiose to glucose

Abstract: Covalent triazine-based frameworks (CTFs) were synthesized in large scale from various monomers. The materials were post-synthetically modified with acid functionalities via gas-phase sulfonation. Acid capacities of up to 0.83 mmol g À1 at sulfonation degrees of up to 10.7 mol% were achieved. SulfonatedCTFs exhibit high specific surface area and porosity as well as excellent thermal stability under aerobic conditions (>300 C). Successful functionalization was verified investigating catalytic activity in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Synthesis of CTF1 – 5. CTF materials have been synthesized via ionothermal synthesis in quartz glass ampules according to literature procedures [22]. In a general procedure, CTF1 – 3 were prepared as follows: 3 g of the selected monomer ( I , II or III ) were thoroughly mixed and finely ground with 5 equiv of ZnCl 2 within a glovebox and transferred into a quartz ampule (12 cm height and 3 cm diameter).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of CTF1 – 5. CTF materials have been synthesized via ionothermal synthesis in quartz glass ampules according to literature procedures [22]. In a general procedure, CTF1 – 3 were prepared as follows: 3 g of the selected monomer ( I , II or III ) were thoroughly mixed and finely ground with 5 equiv of ZnCl 2 within a glovebox and transferred into a quartz ampule (12 cm height and 3 cm diameter).…”
Section: Methodsmentioning
confidence: 99%
“…Gas adsorption measurements. In a similar manner as described before [22], nitrogen physisorption experiments were conducted on a Micromeritics ASAP 2010 instrument. Samples were degassed for at least 15 h at 150 °C using a FloVacDegasser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for starch as substrate, the hydrolysis rate was lower than that of inulin, which is not only related to the degree of polymerization, but also to the type of glycosidic bond; for that, the β (2–1) glycosidic bond of inulin is considered to be easier to hydrolyze than the α (1–4) glycosidic bond of starch 1,42,43 . The hydrolysis ratio remained unchanged in the later stage and this may be due to the pores of the catalyst being blocked by adsorbing of substrate/product with reaction time prolongation, resulting in the hydrolysis ratio not changing 41 . The above results show that ATP‐S has good catalytic activity in hydrolysis reactions under water solution, and the generated monomers are quite stable in this mild system.…”
Section: Resultsmentioning
confidence: 99%
“…However, the hydrolysis ratios of xylan, maltose, and cellobiose did not change in the later stage of the experiments; this may be because the average pore diameter of the catalyst is 3.178 nm, which is easily blocked by adsorbing of substrate/product with reaction time prolongation, resulting the hydrolysis ratio not changing. 41 From the data described above, it can be concluded that hydrolysis efficiency depends not only on the type of bond but also on the polymerization degree of the reactant.…”
Section: Bet Analysismentioning
confidence: 98%